Meta-analysis on The Effects of Hypertension, Type II Diabetes Mellitus, and Smoking on the Risk of Stroke among Asian Young Adult Population - Windhy Monica; Vitri Widyaningsih; Endang Sutisna Sulaeman (Masters Program in Public Health, 2019)
Background: The incidence of stroke at a young age is reported to increase. Stroke at a young age is still often found in classic risk factors that can be changed such as hypertension, dyslipidemia, and type II diabetes mellitus (type II DM). Control of the right risk factors will affect the incidence of stroke. This study aims to analyze stroke risk factors in young populations in Asia.Subjects and Method: This study is a meta-analysis carried out using PRISMA systematic guide